Field emission scanning electron microscopy (FE-SEM) as an approach for nanoparticle detection inside cells - Havrdova, M; Polakova, K; Skopalik, J; Vujtek, M; Mokdad, A; Homolkova, M; Tucek, J; Nebesarova, J; Zboril, R (Micron, 2014)
When developing new nanoparticles for bio-applications, it is important to fully characterize the nanoparticle's behavior in biological systems. The most common techniques employed for mapping nanoparticles inside cells include transmission electron microscopy (TEM) and scanning transmission electron microscopy (STEM). These techniques entail passing an electron beam through a thin specimen. STEM or TEM imaging is often used for the detection of nanoparticles inside cellular organelles. However, lengthy sample preparation is required (i.e., fixation, dehydration, drying, resin embedding, and cutting). In the present work, a new matrix (FTO glass) for biological samples was used and characterized by field emission scanning electron microscopy (FE-SEM) to generate images comparable to those obtained by TEM. Using FE-SEM, nanoparticle images were acquired inside endo/lysosomes without disruption of the cellular shape. Furthermore, the initial steps of nanoparticle incorporation into the cells were captured. In addition, the conductive FTO glass endowed the sample with high stability under the required accelerating voltage. Owing to these features of the sample, further analyses could be performed (material contrast and energy-dispersive X-ray spectroscopy (EDS)), which confirmed the presence of nanoparticles inside the cells. The results showed that FE-SEM can enable detailed characterization of nanoparticles in endosomes without the need for contrast staining or metal coating of the sample. Images showing the intracellular distribution of nanoparticles together with cellular morphology can give important information on the biocompatibility and demonstrate the potential of nanoparticle utilization in medicine.
Keywords: Nanoparticles; Mesenchymal Stem Cells; lidé; mikroskopie elektronová rastrovací; mezenchymální kmenové buňky; magnetické nanočástice; Magnetite Nanoparticles; Microscopy, Electron, Scanning; nanočástice; Humans